2020
DOI: 10.3390/insects11080459
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Increase in CO2 and Temperature Alters Wheat Growth and Aphid Performance Differently Depending on Virus Infection

Abstract: Climate change impacts crop production, pest and disease pressure, yield stability, and, therefore, food security. In order to understand how climate and atmospheric change factors affect trophic interactions in agriculture, we evaluated the combined effect of elevated carbon dioxide (CO2) and temperature on the interactions among wheat (Triticum aestivum L.), Barley yellow dwarf virus species PAV (BYDV-PAV) and its vector, the bird cherry-oat aphid (Rhopalosiphum padi L.). Plant traits and aphid biological pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 87 publications
2
20
0
Order By: Relevance
“…In our study, eCO 2 significantly increased tiller number and aboveground dry biomass, which is consistent with previous findings (Bloom et al, 2010;Taub, 2010;Trębicki et al, 2016;Walker et al, 2017;Moreno-Delafuente et al, 2020). The observed eCO 2 -induced reduction in leaf chlorophyll content (a proxy for plant N content) has also been noted by others (Myers et al, 2014;Ryan et al, 2014;Dáder et al, 2016;Trębicki et al, 2016; Vassiliadis et al, 2018;Moreno-Delafuente et al, 2020). The mechanisms responsible for such a reduction are not fully understood, though Myers et al (2014) proposed that it may be due to a combination of factors including carbohydrate dilution, slower N uptake in the roots and decreased transpiration-driven N flow, among others.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, eCO 2 significantly increased tiller number and aboveground dry biomass, which is consistent with previous findings (Bloom et al, 2010;Taub, 2010;Trębicki et al, 2016;Walker et al, 2017;Moreno-Delafuente et al, 2020). The observed eCO 2 -induced reduction in leaf chlorophyll content (a proxy for plant N content) has also been noted by others (Myers et al, 2014;Ryan et al, 2014;Dáder et al, 2016;Trębicki et al, 2016; Vassiliadis et al, 2018;Moreno-Delafuente et al, 2020). The mechanisms responsible for such a reduction are not fully understood, though Myers et al (2014) proposed that it may be due to a combination of factors including carbohydrate dilution, slower N uptake in the roots and decreased transpiration-driven N flow, among others.…”
Section: Discussionsupporting
confidence: 93%
“…This supports that different insectplant models respond differently to eCO 2 (Ryalls and Harrington, 2016). Several studies have reported an increase in aphid fecundity (Jiang et al, 2018) and abundance (Ryan et al, 2015), while others a decrease in aphid fecundity under eCO 2 (Newman et al, 1999;Awmack et al, 2004;Oehme et al, 2013;Ryan et al, 2014;Dáder et al, 2016;Trębicki et al, 2016;Moreno-Delafuente et al, 2020). Although we found that eCO 2 significantly decreased the fecundity of the bird cherry-oat aphid, it was overall lower than that reported by Trębicki et al (2016) on the same insectplant model and under similar conditions (controlled plant growth chambers set at 20°C; aCO 2 = 385 ppm and eCO 2 = 650 ppm).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations